Ethno-botanical Survey of Garcinia Species of Assam - Gogoi, B.; Das, R. P.; Barua, U.; Boruah, R. (International Journal of Bio-resource and Stress Management, 2023)
An ethno-botanical study of Garcinia species of Assam viz., Garcinia pedunculata Roxb, Garcinia cowa Roxb, Garcinia lanceaefolia Roxb and Garcinia xanthochymus Hook. was conducted during the period of 2012−14. The five districts of Assam i.e. Dibrugarh, Sivsagar, Jorhat, Golaghat and Nagaon were selected purposively for ethno-botanical survey of the selected species and the data were collected personally through interview method in the residence of the respondents. The ethno-botanical study revealed that majority of people uses the fruits of all the four species for different purposes than the seed, leaf and bark. However, most of the people from the five districts used these Garcinia plant as a source of medicine and for some social customs like in Bohag bihu, Garcinia pedunculata is used for bathing purpose. The people of all five districts mentioned that infusion of dry pericarp of Garcinia cowa and Garcinia pedunculata is used for curing diarrheal, dysentery and flatulence. The fruits of Garcina pedunculata were effective to cure jaundice and the leaves of Garcinia lanceaefolia is used as vegetables and sometimes people are using the trunk and leaf of the fruit plants as wood and fodder respectively. The wood of Garcinia xanthochymus is used for making traditional rice mill ‘Dheki’. All the four species were mostly grown in the backyard garden as semi-wild condition and all the respondents believed that these species are indigenous to Assam.